Ticagrelor, but not clopidogrel, reduces arterial thrombosis via endothelial tissue factor suppression. Issue 1 (15th November 2016) - Reiner, Martin F.; Akhmedov, Alexander; Stivala, Simona; Keller, Stephan; Gaul, Daniel S.; Bonetti, Nicole R.; Savarese, Gianluigi; Glanzmann, Martina; Zhu, Cuicui; Ruf, Wolfram; Yang, Zhihong; Matter, Christian M.; et al.
Abstract : Aims: The P2Y12 antagonist ticagrelor reduces mortality in patients with acute coronary syndrome (ACS), compared with clopidogrel, and the mechanisms underlying this effect are not clearly understood. Arterial thrombosis is the key event in ACS; however, direct vascular effects of either ticagrelor or clopidogrel with focus on arterial thrombosis and its key trigger tissue factor have not been previously investigated. Methods and results: Human aortic endothelial cells were treated with ticagrelor or clopidogrel active metabolite (CAM) and stimulated with tumour necrosis factor-alpha (TNF-α); effects on procoagulant tissue factor (TF) expression and activity, its counter-player TF pathway inhibitor (TFPI) and the underlying mechanisms were determined. Further, arterial thrombosis by photochemical injury of the common carotid artery, and TF expression in the murine endothelium were examined in C57BL/6 mice treated with ticagrelor or clopidogrel. Ticagrelor, but not CAM, reduced TNF-α-induced TF expression via proteasomal degradation and TF activity, independently of the P2Y12 receptor and the equilibrative nucleoside transporter 1 (ENT1), an additional target of ticagrelor. In C57BL/6 mice, ticagrelor prolonged time to arterial occlusion, compared with clopidogrel, despite comparable antiplatelet effects. In line with our in vitro results, ticagrelor, but not clopidogrel, reduced TF expression in the endothelium of murine arteries. Conclusion: Ticagrelor, unlike clopidogrel, exhibits endothelial-specific antithrombotic properties and blunts arterial thrombus formation. The additional antithrombotic properties displayed by ticagrelor may explain its greater efficacy in reducing thrombotic events in clinical trials. These findings may provide the basis for new indications for ticagrelor.